Swarm optimization based on-chip inductor optimization - Mandal, S.K.; Goyel, A.; Gupta, A. (CODEC : 2009 4th International Conference on Computers and Devices for Communication : 14-16 December 2009, 2009)
On-Chip spiral inductors are the essential component of radio frequency integrated circuits (RFIC). The major bottleneck of RFIC design automation is the efficient parameterized synthesis of spiral inductors. RFIC designers always require inductors of maximum quality factor (Q) for a given inductance value. To find geometry parameters of spiral inductors of maximum quality factor subject to some constraints, numbers of local and global nonlinear techniques have been proposed. In this paper a particle swarm optimization (PSO) algorithm based approach for layout synthesis of spiral inductors is presented. Constraint handling is based on simple preserving feasibility rules. Results indicate that the PSO based approach can find optimal spiral inductor layout geometries rapidly with enhanced quality factor.